Primitive Virtualities and Historical Actualisations in the Dance of Pina Bausch. For a Sociology of the Archetype - De Feo, Linda (Italian Sociological Review, 2026)
This reflection is founded upon the indissoluble connection between archetypal transcendence and archetypal immanence. It is hypothesized that the archetypes of the collective unconscious, identified by Carl Gustav Jung, can be historicized and that, therefore, their unfolding in the world can be the object of sociological analysis. This examination focuses on archetypal formulas which coincide with choreographic expressions. The focus will be on one of the effects of the development of the Western Terpsichorean model. The latter originated in the vital core of the dithyrambic chorus, the place of the first imaginative manifestation of the emancipation of the human subject from animalitas. An ideal thread connects the gestures of the chorus members disguised as satyrs, who inherit the primordial scream, to the subsequent articulations of the history of dance. That scream resonates in all the artistic turning points that reflect the epochal junctures marked by the crisis of value systems. From such traumas emerges the reactivation of archetypal cores. This paper aims to highlight the importance of the conjunctions between aesthetic inspiration and analytical intent promoted by Tanztheater, founded in the seventies of the twentieth century and following the trail already traced by the German expressionist dance of the twenties. Particular attention is dedicated to the work of an influential figure in dance theater, Pina Bausch, and her transposition of archetypal elements into the rhythm of collective, erotic, political, and sacred dance rituals. The choreographer revolutionises academic codifications by creating figurations in which dancers mime and interpret the ordinariness of everyday movements. She captures the contradictions generated in individuals and society by the archetypal polarisation between meaning and meaninglessness, pacification and conflict, good and evil, life and death, antinomies that will find their full expression in the subsequent traumas represented by the post-organic transgressions of the performance.